Adenomatoid Tumor: Epididym - Yekeler, Hayreddin; Bozlak, Nurten; Orhan, İrfan; Akpolat, Nusret; Ergin, Ertürk (Fırat University, 2001)
Adenomatoid tumor is a benign neoplasm of the male and female genital tract. Epididymis is the most common site of involvement. Most of the patients are in their 3rd and 4th decades and have a firm, sometimes painfull mass in their scrotum. Our patient had painless palpable mass in his left site of scrotum for past 1,5 years and diagnosed as adenomatoid tumor. It was suggested that it was useful to make correct diagnosis and discuss the differentiation of adenomatoid tumor in eliminating the anxiety and indefiniteness in both patient and doctor.

Adenomatoid tümör erkek ve kadın genital sisteminin benign bir neoplazmıdır. Epididim en sık görüldüğü alandır. Hastaların çoğu yaşamlarının 3.-4. dekadlarındadır ve skrotum içinde, sert, bazen ağrılı olabilen kitle mevcuttur. Birbuçuk yıldır skrotumun solunda ağrısız kitlesi olan hasta epididimin adenomatoid tümörü tanısı aldı. Adenomatoid tümörün ayırıcı tanısının önemi ve doğru tanının hem hasta, hemde doktor üzerindeki anksiyete ve belirsizliği ortadan kaldırması açısından tartışılmaya değer bulunmuştur.
ADENOMATOİD TÜMÖR: EPİDİDİM (OLGU SUNUMU)